2017
DOI: 10.1248/bpb.b16-00828
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid Suppresses the Bitter Taste of Olopatadine Hydrochloride Orally Disintegrating Tablets

Abstract: Orally disintegrating tablets (ODTs) are formulated to disintegrate upon contact with saliva, allowing administration without water. Olopatadine hydrochloride, a second-generation antihistamine, is widely used for treating allergic rhinitis. However, it has a bitter taste; therefore, the development of taste-masked olopatadine ODTs is essential. Some studies have suggested that citric acid could suppress the bitterness of drugs. However, these experiments were performed using solutions, and the taste-masking e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Fourier transform-infrared (FTIR) spectroscopy FTIR results of the raw materials and the CBD-ODFs can be found in Figures 2 and 3 and Table III. The substances analysed were: CBD-a cannabinoid, Hypromellose-Vivapharm HPMC E3 , CA-used as a taste-masking agent [20], saliva stimulating agent [4] while other studies showed that it could be used as a plasticizer [18], SRB-a non-cariogenic sweetener [26], PFL-taste masking agent and flavouring agent. The other two spectra belonged to the ODFs.…”
Section: Structural Analysismentioning
confidence: 99%
“…Fourier transform-infrared (FTIR) spectroscopy FTIR results of the raw materials and the CBD-ODFs can be found in Figures 2 and 3 and Table III. The substances analysed were: CBD-a cannabinoid, Hypromellose-Vivapharm HPMC E3 , CA-used as a taste-masking agent [20], saliva stimulating agent [4] while other studies showed that it could be used as a plasticizer [18], SRB-a non-cariogenic sweetener [26], PFL-taste masking agent and flavouring agent. The other two spectra belonged to the ODFs.…”
Section: Structural Analysismentioning
confidence: 99%
“…It has been reported that the addition of flavor improves the sweetness of famotidine ODT and amlodipine ODT. 19,22) Generally, taste masking is adjusted to a certain target drug during ODT development. When two different ODTs are taken simultaneously, the respective flavoring agents might not be appropriate for drugs other than the target drug, which may greatly worsen palatability.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the bitterness, sweetness and overall palatability of the ODTs were evaluated using a VAS (first evaluation). [19][20][21][22][23] Bitterness VAS scores of 0 and 100 indicate "none" and "very bitter," sweetness scores of 0 and 100 indicate "none" and "very sweet," and overall palatability VAS scores of 0 and 100 indicate "bad" and "good," respectively. In parallel with the VAS evaluation, the clinical disintegration time was measured using a stopwatch.…”
Section: Methodsmentioning
confidence: 99%
“…The result precludes a general anti histamine effect, instead strengthening the bitter taste theory. Olopatadine [9] and desloratadine [10], both known for their bitter taste, relaxed airway segments in a way that resembled the effects of MP-AzeFlu and azelastine ( Fig. 1c, d).…”
Section: Open Accessmentioning
confidence: 99%